Designing the sustainable broken case manual order picking operation in the finished goods warehouse of the frozen processed seafood industry - Arachaphon Thairach; Sirirat Suwatcharachaitiwong; Sivasit Wittayasilp; Laksiri Treeranurat; Panupong Vichitkunakorn; Nikorn Sirivongpaisal (International Journal of Sustainable Engineering)
The design of sustainable warehouses has significant importance, influencing economic, social, and environmental dimensions. Order picking represents a key operation within a warehouse, and an effective design directly affects its sustainability performance. The objective of this investigation is to present a case study of a small and medium-sized frozen seafood warehouse focusing on designing the broken case manual order picking operation to achieve multiple performance optimisations under the sustainability framework. The key performance indicators, including Rack Utilisation, Labour Utilisation, and Total Picking Time (TPT), while employing experimental design and simulation techniques to analyse influential factors, were considered within the perspective of the work. The findings indicate that the pursuit of sustainability necessitates a careful balance among economic, social, and environmental considerations concerning proper order picking factors. Significant factors, including batch picking and fixed storage assignment, yielding a composite desirability function of 0.2953, having target settings of 80% for both labour and rack utilisation, and a total picking time of 25 minutes, were determined for the optimum configuration parameters. Based on the findings of this work, the data could have a potential value to validate, illustrate, or extend theories applicable to other warehouses and similar research fields to enhance warehouse sustainability.